Iron-sulfur clusters are involved in post-translational arginylation - Verna Van; Janae B. Brown; Corin R. O’Shea; Hannah Rosenbach; Ijaz Mohamed; Nna-Emeka Ejimogu; Toan S. Bui; Veronika A. Szalai; Kelly N. Chacón; Ingrid Span; Fangliang Zhang; Aaron T. Smith (Nature Communications, 2023)
The enzyme ATE1 catalyzes eukaryotic post-translation arginylation, a key protein modification necessary for cellular homeostasis. Here, the authors show that ATE1s are previously unrealized iron-sulfur proteins that use this oxygen-sensitive inorganic cofactor to control cellular arginylation